2000
DOI: 10.1007/s004210050033
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of treadmill and cycle ergometer tests in triathletes, runners and cyclists

Abstract: The objective of this study was to evaluate the viability of using a single test in which cardiorespiratory variables are measured, to establish training guidelines in running and/or cycling training activities. Six triathletes (two females and four males), six runners (two females and four males) and six males cyclists, all with 5.5 years of serious training and still involved in racing, were tested on a treadmill and cycle ergometer. Cardiorespiratory variables [e.g., heart rate (HR), minute ventilation, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 33 publications
9
66
1
3
Order By: Relevance
“…Indeed, it has been traditionally shown that _ VO 2 max is 3-11% lower during cycling than running (Achten et al 2003;Basset and Boulay 2000;Carter et al 2000;Nieman et al 1998). In some studies, however, no significant difference in _ VO 2 max was found between these two modes of exercise (Billat et al 1998;Hermansen and Saltin 1969), which suggests that _ VO 2 max values are also dependent upon the specific training of an athlete (Basset and Boulay 2000). In the present investigation, six of the volunteers were more ''cycling-oriented'' than ''running-oriented'', which may partly explain the similar _ VO 2 max reached during the cycling and running incremental tests.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been traditionally shown that _ VO 2 max is 3-11% lower during cycling than running (Achten et al 2003;Basset and Boulay 2000;Carter et al 2000;Nieman et al 1998). In some studies, however, no significant difference in _ VO 2 max was found between these two modes of exercise (Billat et al 1998;Hermansen and Saltin 1969), which suggests that _ VO 2 max values are also dependent upon the specific training of an athlete (Basset and Boulay 2000). In the present investigation, six of the volunteers were more ''cycling-oriented'' than ''running-oriented'', which may partly explain the similar _ VO 2 max reached during the cycling and running incremental tests.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies preferably tested heart rate values in different exercise modalities relative to V Ç O 2 [1,18,19]. Otherwise, lactate measurements are becoming more popular than spirometric measurements in the field of training prescriptions.…”
mentioning
confidence: 98%
“…Ahmaidi et al (1992), suggest that the differences in the values obtained in the different tests could be related to biomechanical factors and the energy expenditure efficiency, possibly because of the recruitment pattern of fibers, being more efficient for a specific intensity task, and a higher recruitment of type I fibers than type II (Mauger and Sculthorpe, 2012). This suggests that it is insufficient to consider just V O2max as the only variable to qualify performance in high-intensity, intermittent activities (Ueda et al, 2011;Denadai et al, 2004;Bassett and Boulay, 2000).The VT has been used to evaluate performance (Bassett and Boulay, 2000). For example, Ueda et al (2011) showed that the relative and absolute V O2 in the VT was significantly higher in the elite vs. non-elite population in a group of soccer players, in addition to a strong association between the VT and the performance in the YYIR2.…”
mentioning
confidence: 88%
“…The VT has been used to evaluate performance (Bassett and Boulay, 2000). For example, Ueda et al (2011) showed that the relative and absolute V O2 in the VT was significantly higher in the elite vs. non-elite population in a group of soccer players, in addition to a strong association between the VT and the performance in the YYIR2.…”
Section: Peak Oxygen Uptake Ventilatory Threshold and Performance Inmentioning
confidence: 99%